Financial Dependents and Sentencing Outcomes in Federal District Courts: Variation by Race, Ethnicity, and Sex - Testa, Alexander (Criminal justice policy review, 2021)
A voluminous literature has detailed disparities in punishment related to extra-legal characteristics such as race, ethnicity, and sex. However, less research has investigated the specific contexts and conditions under which disparities in punishment emerge. Specifically, limited research to date has examined whether family characteristics influence sentencing both directly, and in interaction with race, ethnicity, and sex. The current study investigates this question using data on federal criminal sentences from the United States Sentencing Commission for fiscal years 2015–2017. Findings demonstrate that providing support for dependents generally has a positive association with the likelihood of being incarcerated and overall sentence length. Moreover, the positive association between support for dependents and punishment severity is concentrated among Black male and Hispanic male defendants. Among minority females and White defendants, having dependents has either a negative or null association with sentencing outcomes. Findings are discussed in the context of contemporary theoretical perspectives of punishment.